Potential Energy Surfaces of 1-Phenyl-1,2- propandione-1-oxime and Its Tautomers - BEKHRADNIA, A.R.; ARSHADI, S. (Asian Journal of Chemistry, 2010)
Potential energy surfaces are found for 1-phenyl-1,2-propandione- 1-oxime (1) and its four tautomers, i.e., 1-nitroso-1-phenyl-1-propen- 2-ol (2), 1-nitroso-1-phenyl-2-propanone (3), 2-hydroxy-1-phenylpropenone oxime (4) and 3-nitroso-3-phenyl-propen-2-ol (5). Calculations are carried out at the Hartree-Fock (HF), Density Functional Theory (B3LYP) and the second-order Moller-Plesset perturbation (MP2) levels of theory using 6-31G* and 6-311G** basis sets. Five conformers, with no imaginary vibrational frequency, are obtained by free rotations around three single bonds of 1: Ph-C(NOH)C(O)CH3, PhC(NOH)-C(O)- CH3 and PhC(N-OH)C(O)CH3. Similarly, eight structures with no imaginary vibrational frequency are encountered upon rotations around three single bonds of 2: Ph-C(NO)C(OH)CH3, PhC(N-O)C(OH)CH3 and PhC(NO)C(-OH)CH3. In the same manner, six minima are found through rotations around three single bonds of 3: Ph-CH(NO)C(O)CH3, PhCH(- NO)C(O)CH3 and PhCH(NO)-C(O)CH3. Two minima are also found through rotations around four single bonds of 4: Ph-C(NOH)C(OH)CH2, PhC(N-OH)C(OH)CH2, PhC(NOH)-C(OH)CH2 and Ph-C(NOH)C (-OH)CH2. Finally, two minima are found through rotations around four single bonds of 5: Ph-CH(NO)C(OH)CH2, PhCH(-NO)C(OH)CH2, PhCH(NO)-C(OH)CH2 and PhCH(NO)C(-OH)CH2. Inter-conversion within the above sets of conformers (of 1, 2, 3, 4 and 5) are probed through scanning (one and/or two dimensional) and/or QST3 techniques. The order of the stability of global minima encountered is: 1 > 3 > 2 > 4 > 5. Hydrogen bonding appears significant in tautomers 2 and 4.